PERAN KELOMPOK TANI TERUBUS DALAM MENINGKATKAN PENDAPATAN PETANI SAYUR DI DESA KUNDUR KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI - Ilmi, Arif; Syahza, Almasdi; Riyantama Isjoni, M. Yogi (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2024)
The aim of this research is to determine the increase in welfare created by the activities of the Terubus farmer group on the income level of vegetable farmers in Kundur Village. The method used is a mixed method. This research is a combination of qualitative methods and quantitative methods. The results of this research are that the Terubus farmer group plays a role in increasing the income of vegetable farmers in Kundur Village, Tebing Tinggi Barat District by increasing vegetable production from 2019 to 2023. The cooperation of members in vegetable production activities contributes to the average income of members of the Terubus farmer group . The Terubus farmer group has a significant relationship with increasing the income of vegetable farmers. This was proven through Chi-Square calculations with the total questionnaire score and income obtained with results <0.001, which means it was significant and the research hypothesis was accepted and there was an increase in income as a result of the role of the Terubus Farmer group.